States of self-stress in symmetric frameworks and applications. (January 2022) - Schulze, Bernd; Millar, Cameron; Mazurek, Arek; Baker, William
Abstract: We use the symmetry-extended Maxwell rule established by Fowler and Guest to detect states of self-stress in symmetric planar frameworks. The dimension of the space of self-stresses that are detectable in this way may be expressed in terms of the number of joints and bars that are unshifted by various symmetry operations of the framework. Therefore, this method provides an efficient tool to construct symmetric frameworks with many 'fully-symmetric' states of self-stress, or with 'anti-symmetric' states of self-stress. Maximising the number of independent self-stresses of a planar framework, as well as understanding their symmetry properties, has important practical applications, for example in the design and construction of gridshells. We show the usefulness of our method by applying it to some practical examples.